MORPHOLOGICAL AND HISTOLOGICAL EFFECTS OF BRUCEINE A ON THE LARVAE OF AEDES AEGYPTI LINNAEUS (DIPTERA: CULICIDAE) - Sutiningsih, Dwi; Mustofa, Mustofa; Satoto, Tri Baskoro Tunggul; Martono, Edhi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study aimed to determine a target of action of bruceine A on the basis of its morphological and histological effects on the larvae of Aedes aegypti Linnaeus. Methods: Bruceine A was isolated from Brucea javanica (L.) Merr. seeds in accordance with the Mangungsong method. Larvae of A. Aegypti (L.) in instar III to the beginning of instar IV were treated with various concentrations of bruceine A. The negative control group did not receive any treatment, whereas the positive control group received 1 ppm temefos. Dead larvae were collected after 24 h of treatment for the examination of morphological and histological changes. Results: The negative control group did not exhibit any morphological and histological changes. Larvae treated with bruceine A, however, had visible damaged heads, cuticles, digestive and respiration tracts, respiratory siphons, and setae, and they were smaller than normal larvae. Larvae treated with temefos exhibited gastrointestinal damage, narrowed breathing tubes, cuticle damage, and detached/damaged seta feathers. The necrosis of gastrointestinal epithelial cells was the major histological change exhibited by larvae treated with various concentrations of bruceine A or 1 ppm temefos. Conclusion: The targets of action of bruceine A in A. aegypti (L.) larvae are the head/caput, cuticle, setae, siphon, and gastrointestinal and respiratory tracts.